Exploration of natural free-hand interaction for shape modeling using leap motion controller - Cui, Jian (2021)
In this paper, we propose a web-enabled shape modeling system with natural free-hand interaction, which can be easily learned by users while imposing least mental load on them. The deformation interface allows for performing various deformations, including stretching, compressing, squeezing, enlarging, twisting and tapering, on shapes interactively mimicking how they are done in real life. The manipulation interface allows an object to be directly grabbed and manipulated with either one or two hands, while also smoothly switching between them. Constrained methods are also provided for precise manipulation. An intuitive metaphor is designed to help the users to discover the interaction techniques by themselves without any manuals or instructions. A rendering pipeline, based on function-based extension of VRML/X3D, is designed with hidden complexity to support the proposed functionalities of the system. Hands motions are captured by Leap Motion controller. The user study proves the naturalness of the modeling system, and its easiness to be learned and remembered.